2002
DOI: 10.1590/s0004-282x2002000100028
|View full text |Cite
|
Sign up to set email alerts
|

Mielopatia por deficiência de vitamina B12 apresentando-se como mielite transversa

Abstract: RESUMO -As manifestações neurológicas associadas à deficiência de vitamina B12 incluem polineuropatia, mielopatia, demência e neuropatia óptica. O diagnóstico laboratorial é feito através da dosagem sérica de cianocobalamina ou homocisteína e da excreção urinária de ácido metilmalônico. No estudo anatomopatológico observa-se na microscopia a destruição da mielina e de axônios vistos na substância branca. A região mais comumente afetada é o cordão posterior cervical e/ou torácico. O acometimento da coluna later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…Neuropathy associated with PA classically involves disease progression, beginning in the cervicothoracic region of the spine,202,441 with upper extremity findings classically occurring before lower extremity findings, followed by peripheral nerve involvement, and lastly, if at all, brain involvement 23,200,203. Dementia is believed to be a late and rare finding of neuropathy associated with PA 19,25,48,203,290.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathy associated with PA classically involves disease progression, beginning in the cervicothoracic region of the spine,202,441 with upper extremity findings classically occurring before lower extremity findings, followed by peripheral nerve involvement, and lastly, if at all, brain involvement 23,200,203. Dementia is believed to be a late and rare finding of neuropathy associated with PA 19,25,48,203,290.…”
Section: Discussionmentioning
confidence: 99%
“…Megaloblastic anemia is present in most cases and in 1/3 of the cases may be absent. 13 Healton et al 10 in a study on 143 patients, who had a vitamin B12 deficiency, observed that 27.4% had normal hematocrit and 23% had a normal MCV. A bone marrow biopsy is usually hyperplastic, with a predominance of red cell precursors.…”
Section: Discussionmentioning
confidence: 97%
“…Kosik et al 12 reported the framework of a young patient with a diagnosis of pernicious anemia with acute transverse myelitis and level at T10 due to vitamin B12 deficiency. Vasconcellos et al 13 in turn, described a severe and fatal reports of transverse myelitis with sensory level, which did not respond to replacement therapy. According to Vasconcellos, the presence of sensory level denotes severe case of vitamin B12 deficiency and may be considered a finding associated with a bad prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Um fator genético tem sido implicado em alguns casos de anemia perniciosa com várias gerações acometidas. Trata-se de uma doença tratável que, se diagnosticada precocemente, apresenta bom prognóstico 20 .…”
Section: Constatou-se Também No Estudo Realizado Naunclassified